Analisis Pengaruh Lingkungan Belajar Fisik terhadap Perilaku Belajar Siswa - Mardiah; Ratna Puspita, Neneng (Buletin Ilmiah Pendidikan, 2023)
This study aims to explore the influence of the physical learning environment on student learning behavior at SDN Parakanmuncang II. Employing a quantitative approach with an observational research design, data were collected from 200 students ranging from grades 1 to 6 through direct observation and questionnaire completion. The results of data analysis indicate that the physical learning environment at the school significantly impacts student learning behavior. The research findings reveal that comfortable, clean classrooms equipped with adequate learning facilities contribute positively to students' learning motivation. Sufficient lighting and comfortable room temperature also play a role in enhancing student concentration during learning. The cleanliness of the learning environment also affects student participation in classroom activities. However, there are several aspects of the physical learning environment that need further attention, such as improving lighting and classroom cleanliness. In the context of educational policy development, the research findings provide a strong foundation for increasing attention to the physical learning environment in school planning and management. Thus, this study makes a significant contribution to enriching our understanding of the importance of the physical learning environment in shaping student learning behavior and underscores the need for investment in improving physical facilities in schools to create a more conducive and supportive learning environment for students.